Insólito, imaginativo, dialético: uma leitura de Liev S. Vigotski: escritos sobre arte - TOASSA, Gisele (Estudos de Psicologia (Campinas), 2023)
The publication of the works by the Soviet writer Liev Semionovich Vygotsky (1896-1934) keeps holding his commentators in check, especially those who wish to convert him into a simple piece on the board of development and learning theories. Liev S. Vygotsky: Writings on Art exhibits an anthology of different texts by the author with the first direct translation from Russian into another language (many of them only recently published in their original language, with the issue of the first volume of Vygotsky’s complete works in 2015).